Comércio bilateral entre os países membros do MERCOSUL : uma visão do bloco através do modelo gravitacional - Gräf, Claudir Olípio (Universidade do Vale do Rio dos Sinos, 2012)
The second wave of regionalism, occurred from the nineties, changed significantly the international trade scenario, with the creation of many Preferential Trading Arrangements (PTA). In a beginning of the 2000, the literature went on to study the effects caused by these arrangements on international trade. The aim of this dissertation is to estimate the potential bilateral trade between MERCOSUR members (Argentina, Brazil, Paraguay and Uruguay) using a gravity model, based on panel data. The potential trade flows were estimated for the year 2009, using data for 1999 to 2009, based in a sample of 67 countries. The estimators which measured the bloc effects in bilateral trade flows, even though significant, do not influence considerably the trade flows. The results show a considerable approximation between the estimate potential flows and the real bilateral trade flows in 2009, with a difference between the potential trade flows and the effective trade of only 3,47%. The trade flows with the larger potential trade were Argentina x Paraguay and Argentina x Uruguay, while the country that the effective trade overcomes the potential flows is Brazil, that in all flows, except Brazil x Paraguay, exceeds its potential flows, both as an importer and as an exporter.
Keywords: Fluxo bilateral de comércio; Mercosul; Modelo gravitacional; Bilateral trade flow; Mercosur; Gravity model; ACCNPQ::Ciências Sociais Aplicadas::Economia